2015
DOI: 10.12740/app/58953
|View full text |Cite
|
Sign up to set email alerts
|

Differences between suicide and non-suicidal self-harm behaviours: a literary review.

Abstract: SummaryThe World Health Organization (WHO) states that suicide is one of the 20 most common causes of death -almost 1 million people across the globe die by suicide every year (data from 21 July 2014) [1]. Suicide is one of the most common causes of death among teenagers [2,3]. Another significant but much less known phenomenon is non-suicidal self-injury (self-harm). Despite the fact that we know much less about self-harm than about suicide, research during the past 10 years has indicated that self-harm occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Second, self-injurious and suicidal behavior were aggregated to reflect overall internal threat in the current study. These behaviors have, however, been shown to be distinct from one another (Halicka & Kiejna, 2015) and should be tested separately in future studies where larger/older sample data and higher prevalence rates facilitate such analyses. Third, SIB at 12 years was informed by parental report while PEs at this age were derived from child self-reports.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Second, self-injurious and suicidal behavior were aggregated to reflect overall internal threat in the current study. These behaviors have, however, been shown to be distinct from one another (Halicka & Kiejna, 2015) and should be tested separately in future studies where larger/older sample data and higher prevalence rates facilitate such analyses. Third, SIB at 12 years was informed by parental report while PEs at this age were derived from child self-reports.…”
Section: Study Limitationsmentioning
confidence: 99%
“…To better understand these individual differences, studies are needed examining the role of risk and protective factors of NSSI and SA, both generally and pertaining to childhood maltreatment specifically (Halicka & Kiejna, 2015 ; Serafini et al, 2017 ). Despite decades of research and recent developments in predictive algorithms, SA are still difficult to predict (Belsher et al, 2019 ; Franklin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 illustrates the levels of self‐injurious behavior. While there is substantial overlap between all of the different aspects of self‐injury measured here, prior research has demonstrated important differences between self‐harming and suicidal behavior in the associated risk factors (Brausch & Gutierrez, 2010; Muehlenkamp & Gutierrez, 2004), prevalence rates (Nock et al, 2008; Swannell et al, 2014) and mortality levels (Halicka & Kiejna, 2015). Past research has also established key sociodemographic and clinical differences between suicide ideators and suicide attempters (May & Klonsky, 2016).…”
Section: Resultsmentioning
confidence: 82%